RUMEN METABOLIT OF BALI CATTLE FED FERMENTED RATION BY BALI CATTLE COLON AND ORGANIC WASTE LIGNOCELLULOLYTIC BACTERIA INOCULLANT - P., Masadji; Cakra, I G. L. O.; Mudita, I M. (Jurnal Peternakan Tropika; Vol 10 No 1 (2022): Vol. 10 No. 1 Tahun 2022; January - april, 2022)
This study aimed to in-vivo analyze the level of rumen fermentation of Bali cattle fed fermented rations by 3 types of lignocellulolytic bacterial inoculants from the Bali cattle colon and organic waste produced by Mudita et al. (2015) namely: inoculants with code BS 12 K 12 ; BS 12 K 1 ; and BS 1 K 12 .The research held at The Research Station Education Farm, Bukit Jimbaran, Badung, Bali and Laboratory of Nutrition and Feed Animal, Faculty of Animal Husbandry, Udayana University in 3 (three) months, with 4 (four) total collection periods. The research has been done by The Latin Square Design, with 4 (four) treatment and 4 periode researching as replicated. The treatments were: RB 0 = bali cattle fed ration fermented without bacteria innoculant (fermented molasses solution as control), RB 1 =bali cattle fed ration fermented bacteri innoculant BS 12 K 12 , RB 2 =bali cattle fed ration fermented bacteri innoculant BS 12 K 1 , and RB 3 =bali cattle fed ration fermented bacteri innoculant BS 1 K 12 . The observation variables on this research are: pH, protozoa population, totally VFA and partial such as acetic acid, propionic acid, and butiric acid, and N-NH 3 on the rumen fluid. The result of this research shows that the bali cattle fed ration fermented by inocullant of bali cattle colon and organic waste lignocellulolytic bacteria had increased (P<0,05) the rumen metabolism rate of bali cattle, especially N-NH 3 , propionatic acid and totally VFA, without effecting the pH and population of protozoa on the bali cattle rumen liquid.   Keywords : Rumen Metabolic , Lygnocellulolitic Bacteria Innoculant , Fermented Ration Bali Cattle Colon Bacteria Isolates , Organic Waste Bacteria Isolates